Thalamic sensory strokes with and without pain: differences in lesion patterns in the ventral posterior thalamus. Issue 8 (13th June 2012) - Krause, Thomas; Brunecker, Peter; Pittl, Sandra; Taskin, Birol; Laubisch, Dinah; Winter, Benjamin; Lentza, Malamati Eleni; Malzahn, Uwe; Villringer, Kersten; Villringer, Arno; Jungehulsing, Gerhard J
Abstract : Objective: Vascular lesions of the posterolateral thalamus typically result in a somatosensory syndrome in which some patients develop central neuropathic post-stroke pain (CPSP). Damage to the spinothalamic tract terminus is assumed to be a prerequisite for thalamic CPSP. At the nuclear level, it remains a matter of debate whether the ventral posterolateral nucleus (VPL) or the posterior portion of the ventral medial nucleus (VMpo) constitutes the decisive lesion site. The hypothesis of the study was that lesion location in thalamic CPSP patients differs from that in thalamic stroke patients without pain, and the aim was to identify whether this difference comprises the VPL and/or the VMpo. Design: 30 patients with chronic thalamic stroke and a persistent contralateral somatosensory syndrome were examined. CPSP patients (n=18) were compared with non-pain control patients. By coregistration of a digitised thalamic atlas with T1 weighted MR images, lesion clusters were allocated to the thalamic nuclei. Results: VPL was affected in both groups, but CPSP lesion clusters comprised the more posterior, inferior and lateral parts of the VPL compared with controls. Additional partial involvement of the VMpo was seen in only three pain patients. In three other pain patients, lesions involved neither the VPL nor the VMpo, but mainly affected the anterior pulvinar. Conclusion: This study specifies the role of the VPL in thalamic CPSP and shows that the posterolateratal and inferior parts in particular are critically lesioned in pain patients. In this thalamic subregion, afferents of the spinothalamic tract are known to terminate. In contrast, the data do not support a pivotal impact of the VMpo on thalamic CPSP.